Endometrial fluid aspiration immediately prior to embryo transfer does not affect IVF/vitrified-warmed embryo transfer outcomes – a prospective matched cohort study. Issue 3 (March 2022) - Hou, Zhaojuan; He, Aihua; Zhang, Qiong; Liu, Nenghui; Liu, Donge; Li, Yumei; Xu, Bin; Wang, Yonggang; Li, Shuyi; Tian, Fen; Liao, Tingting; Zhang, Yeqing; et al.
Abstract: Research question: Does the endometrial aspiration of ultrasound-invisible fluid immediately preceding embryo transfer affect IVF/vitrified-warmed embryo transfer outcomes? Design: A prospective matched cohort study was conducted in 96 women and 96 control participants to assess the effect on pregnancy outcomes of endometrial aspiration performed immediately before embryo transfer. This study was carried out at a university-affiliated assisted reproductive medical centre between January 2019 and December 2019. Patients were divided into two groups. The EA group had cycles with endometrial aspiration of ultrasound-invisible fluid performed before embryo transfer and the non-EA group featured cycles without endometrial aspiration. The EA group was matched by propensity score with the non-EA group in a 1:1 ratio. The EA group consisted of 99 participants before and 96 participants after propensity score matching. There were 203 and 96 participants in the non-EA group before and after propensity score matching. Results: No significant differences were detected in the baseline characteristics and cycle characteristics of the EA and non-EA groups. No significant between-group differences were found in reproductive outcomes in the overall population. Subgroup analysis of blastocyst transfer cycles showed the implantation rate was significantly higher in the EA group (61 women per group, 57.1% versus 40.8%, relative risk 1.40, 95% confidence interval 1.04–1.88; P = 0.022). Live birth rate, clinical pregnancy rate, ongoing pregnancy rate and multiple pregnancy rate were not different among the groups. Conclusions: Endometrial aspiration immediately preceding embryo transfer does not affect IVF/vitrified-warmed embryo transfer outcomes. Interestingly, it might improve the vitrified-warmed blastocyst implantation rate. Randomized controlled trials are needed to confirm this result.